National security and foreign relations challenges: kidnapping issue in Nigeria (2006-2018) - Ibrahim, Yusuf Kamaluddeen
Nigeria is a complex society with a rapid population growth of over 200 million people comprising of 250 distinct ethnic groups with over 500 different languages. Thus, uniting these numerous groups into one unified political entity since the amalgamation of Nigeria in 1914 is an enormous task. Apart from other social vices that accounted for the protracted state of Nigeria problem, Nigeria has plunged into waves of kidnapping, banditry, armed robbery, and Boko Haram insurgence perpetrating almost every part of the country. Although, the menace of kidnapping in Nigeria started in the Niger delta in 2006, the number of cases deteriorated in Nigeria from 2007 to 2018, in which several people have been kidnapped. On foreign relations, beside local people, kidnappers have kidnapped several foreign expatriates working for multinational oil companies. The kidnappers demanded either for ransom or a reciprocal for releasing their member being capture by the authority's or other demands. Therefore, this study aims to analyse the root causes of kidnapping in Nigeria and its implications on the national security and foreign relations of Nigeria. The objectives of the study were achieved using a qualitative approach. The data were collected through semi-structured interviews with 10 participants comprising of security personnel, victims and academicians., as well as official documents, books, journals, dissertations, and other unpublished manuscripts. The data were analyzed using the Braun and Clarke's six stages of thematic analysis with the aid of Qualitative Data Analysis software, i.e., Atlas. ti. The study found that kidnapping posed an immense threat to Nigerian national security with deprivation of the constitutional right of movement and imposed post-traumatic stress disorder on the victims. The foreign relations impact of kidnapping involves inhibition of tourism, deterrence of foreign investment, and inflicting Nigeria into a visa-banned nation by some foreign nations. The findings also revealed that the negligence of the Nigerian government to address the root-causes of kidnapping, such as unemployment and abject poverty, resulted to the force-driven security threat in the country. Despite the efforts made by the security agencies to tackle the menace of heinous crimes in Nigeria, kidnapping is evolving with a massive impact on the socio-economic development of the country. Some policies, institutional and legislative recommendations were offered by this study in order to stem the tide of kidnapping in the country. This study offers great importance to the policymakers in tackling kidnapping cases. It will also assist the government to establish good relations with foreign nations to come together, forged ahead, and coordinate to bring the perpetrators to justice so that foreign partners and international bodies will see the efforts in curtailing and stemming the tide of kidnapping in Nigeria as a success.